Penguatan Empati Sosial melalui Kunjungan Edukatif ke Masyarakat Adat Baduy Luar - Mawaddatul Ulya; Anggita Nurcahyani; Muadz Muadz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This activity aims to strengthen students’ social empathy through an experiential learning approach combined with indigenous community engagement. The program was initiated in response to the declining social sensitivity among students in the digital era, where individualism often dominates social interactions. Therefore, contextual and reflective learning experiences are needed to develop students’ humanistic character. The educational visit was conducted in the Baduy Luar indigenous community, Kanekes Village, Lebak Regency, Banten, involving students from various study programs. The methods included participatory observation, informal interviews, and written reflections analyzed using a descriptive qualitative approach. The results showed that students demonstrated increased empathy and cross-cultural awareness through direct interaction with the community. They learned the values of simplicity, mutual cooperation, and harmony between humans and nature. Beyond enhancing student awareness, the activity also strengthened collaborative relations between higher education institutions and indigenous communities as equal learning partners. Thus, experiential learning proved effective in fostering social empathy and humanitarian awareness among students.